2018
DOI: 10.1016/j.psychres.2018.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Clinical predictors of gaming abstinence in help-seeking adult problematic gamers

Abstract: Research into the effectiveness of interventions for problematic gaming has been limited by a lack of data concerning the clinical characteristics of voluntary treatment-seekers; the nature and history of their gaming problems; and, their reasons for seeking help. The study aimed to identify variables predictive of short-term commitment to gaming abstinence following initial voluntary contact with an online help service. A total of 186 adult gamers with gaming-related problems were recruited online. Participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 58 publications
1
17
1
2
Order By: Relevance
“…The checklist has been used in clinical and neurobiological studies of GD, and shown solid psychometric qualities ( King et al, 2020b , King et al, 2020c ). Internal consistency of the scale in this study was 0.68, which was relatively low but consistent with other studies ( Evans et al, 2018 , Jeromin et al, 2016 , King et al, 2018 ), and which may be attributed to the variable sensitivity of the 9 DSM-5 criteria ( Ko et al, 2014 ).…”
Section: Methodssupporting
confidence: 90%
“…The checklist has been used in clinical and neurobiological studies of GD, and shown solid psychometric qualities ( King et al, 2020b , King et al, 2020c ). Internal consistency of the scale in this study was 0.68, which was relatively low but consistent with other studies ( Evans et al, 2018 , Jeromin et al, 2016 , King et al, 2018 ), and which may be attributed to the variable sensitivity of the 9 DSM-5 criteria ( Ko et al, 2014 ).…”
Section: Methodssupporting
confidence: 90%
“…Some studies (Zhang et al, 2016a,b, 2018; Deng et al, 2017; King et al, 2018) were considered at risk for selection bias, because the allocation in the experimental or control group was not random, or because the experimental group was made up only of patients who agreed to participate from a clinical community. In all the studies, it was not possible to estimate performance bias because the blinding procedure of participants and personnel could not be applied because only one of the groups received an intervention (e.g., clinical group vs. healthy group).…”
Section: Resultsmentioning
confidence: 99%
“…A risk of detection bias was also reported in one study (Eickhoff et al, 2015) because the outcomes were exclusively based on the reports of the same therapist that conducted the intervention. A number of studies (Eickhoff et al, 2015; van Rooij et al, 2017; Zhang et al, 2016a,b, 2018; King et al, 2018) could have a risk for attrition bias because intervention data were incomplete, or quite large numbers of missing or incomplete data were detected. Some studies (Eickhoff et al, 2015; Park et al, 2016b, 2017; Vasiliu and Vasile, 2017) showed reporting bias because not all the information about outcome and the evaluation of the treatment were reported, or because effect sizes were not reported.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, individual factors related to GD may delay or inhibit treatment seeking, such as low insight, procrastination, impulsivity, and shyness or introversion (43)(44)(45)(46). Another possibility is that some individuals with gaming-related problems may initially seek out information, social support and assistance from less formal, convenient sources, such as online support groups (47).…”
Section: Introductionmentioning
confidence: 99%